Isolation, molecular characterization, and in vitro schizogonic development of Sarcocystis sp. ex Accipiter cooperii from a naturally infected Cooper's hawk (Accipiter cooperii). Issue 2 (April 2017) - Lindsay, David S.; Verma, Shiv K.; Scott, David; Dubey, Jitender P.; von Dohlen, Alexa R.
Abstract: Raptors serve as the definitive host for several Sarcocystis species. The complete life cycles of only a few of these Sarcocystis species that use birds of prey as definitive hosts have been described. In the present study, Sarcocystis species sporocysts were obtained from the intestine of a Cooper's hawk ( Accipiter cooperii ) and were used to infect cell cultures of African green monkey kidney cells to isolate a continuous culture and describe asexual stages of the parasite. Two clones of the parasite were obtained by limiting dilution. Asexual stages were used to obtain DNA for molecular classification and identification. PCR amplification and sequencing were done at three nuclear ribosomal DNA loci; 18S rRNA, 28S rRNA, and ITS-1, and the mitochondrial cytochrome c oxidase subunit 1 ( cox1 ) locus. Examination of clonal isolates of the parasite indicated a single species related to S. columbae (termed Sarcocystis sp. ex Accipiter cooperii ) was present in the Cooper's hawk. Our results document for the first time Sarcocystis sp. ex A. cooperii occurs naturally in an unknown intermediate host in North America and that Cooper's hawks ( A. cooperii ) are a natural definitive host. Highlights: Sarcocystis sp. ex Accipiter cooperii related to Sarcocystis columbae was isolated from a Cooper's hawk from the USA. Cloning of asexual stages andmolecular analysis demonstrated that only one species was present in the Cooper's hawk. Asexual stages were grown in mammalian cell cultures. PCR amplification and sequencing of 18S rRNA, 28S rRNA, ITS-1, and ( cox1 ) loci demonstrated the parasite was closely related to S. columbae . Graphical abstract: